ANALISIS STAKEHOLDER DALAM PROGRAM SWASEMBADA PANGAN DI WILAYAH (PROGRAM UPSUS PAJALE DI KABUPATEN BENGKULU UTARA) - Hafid, Achmad; Munandar, Adis Imam (Jurnal AGRISEP, 2019)
This study aims to determine the role and level of importance, level of strength and level of legitimacy in food self-sufficiency programs implemented in the region. Food self-sufficiency is a food security program that is very important so that the program involves many stakeholders and the role of each stakeholder in the success of the program. This study uses a stakeholder management approach in the data analysis used. This research was conducted in North Bengkulu Regency in the UPSUS PAJALE program. The results of the study are the role of the local government stakeholders, the Food Crops and Extension Agency has a high level of importance, strength and level of legitimacy compared to other stakeholders so that the level of coordination and collaboration between stakeholders is needed so that the UPSUS PAJALE program can run smoothly and successfully.